Risk factors for complications after skin-sparing and nipple-sparing mastectomy - Paprottka, Felix Julian; Schlett, Christopher L.; Luketina, Rosalia (Breast care, 2019)
Introduction: In order to achieve a complication-free breast reconstruction, it is fundamental for each individual patient case to determine preoperatively certain risk factors that might have a negative impact on the postoperative result after skin-sparing (SSM) or nipple-sparing mastectomy (NSM). Methods: A retrospective study of 39 female breast cancer patients who received SSM or NSM breast reconstruction in our department (time interval: 2010-2015), was performed. The study focus is on determining patient characteristics (e.g., demographics, history of radiotherapy/chemotherapy, menopausal status, amount of resected breast tissue) leading to higher complication rates. Results: Overall, 50 mastectomies (27 SSM and 23 NSM) with 6 immediate and 35 immediate 2-stage tissue expander breast reconstructions amounting to a total of 41 surgical interventions (n = 41) were carried out. Median follow-up time was 2 years and 5 months (range 121-1,863 days). Increased complication rates were associated with the following patient characteristics: age >50 years (p < 0.05) and personal history of cardiovascular disease (p < 0.05). Increased but not significant risk factors included postmenopausal status (p = 0.07), radiotherapy prior to SSM/NSM (p = 0.06), and weight of resected breast tissue >438 g (p = 0.09). Conclusion: This work identified age >50 years and personal history of cardiovascular disease to be risk factors for increased complication rates following SSM and NSM. Therefore, the given findings should be taken into account when selecting patients for these 2 procedures.
Gesehen am 11.12.2019